A175 BEHAVIORAL INTERVENTIONS TO ADDRESS INFLAMMATORY BOWEL DISEASE-RELATED DISTRESS AND QUALITY OF LIFE: A SYSTEMATIC REVIEW AND META-ANALYSIS. (4th March 2021) - Reise-Filteau, M; Heisler, C; Shepherd, T; Stewart, M J; Jones, J
Abstract: Background: Inflammatory bowel disease-associated psychological distress (IBD-PD) (inclusive of anxiety, depression, and high levels of stress) is prevalent amongst persons living with IBD. IBD-PD impairs quality of life (QoL) and worsens disease outcomes. Research relating to the efficacy of behavioral interventions for IBD-PD has been limited. Aims: This systematic review and meta-analysis was conducted to evaluate the efficacy of cognitive behavioral therapy (CBT)-based interventions for the management of IBD-PD and QoL in persons living with IBD. Methods: Pre-defined criteria were used to identify randomized controlled studies reporting on the efficacy of CBT-based interventions for IBD-PD and QoL in adults living with IBD. Electronic databases including CINAHL, Cochrane Library, Embase, MEDLINE, PsycArticles, PsycInfo, Pubmed, and Web of Science were searched from inception to May 30, 2020. Studies published in English or French were included. Risk of bias was assessed using the Cochrane risk-of-bias tool by two independent reviewers (CH and MRF). Data was extracted and summarized qualitatively. A random-effects model was used to generate pooled estimates. Results: Eight studies (922 participants) met criteria for inclusion in this review. The studies evaluated outcomes of quality of life and IBD-PD using the IBD Questionnaire (IBDQ), United Kingdom IBDQ, Short IBSQ, 36-Item Short Form Survey (SF-36), Short Health Scale, Perceived Stress Questionnaire (PSQ), Perceived Stress Scale (PSS-10), Hospital anxiety depression scale (HADS) and the Depression, Anxiety and Stress Scale-21 Items (DASS-21). Of the 8 studies, 2 were low, 2 high, and 4 at intermediate risk of bias. Interventions, duration, and outcome assessments differed across studies and observed attrition rates were high. The pooled odds ratio for the short-term impact of CBT on IBDQ (n=3) was 0.30 (95% CI 0.17- 0.44) favoring CBT. Perceived stress (PSQ and PSS-10) were only reported in 3 studies as secondary outcomes. Overall, CBT had no observed benefit for perceived stress. Measurement of anxiety and depression was inconsistent across studies. The impact of CBT on anxiety and depression varied with studies revealing both neutral and positive results. Conclusions: In patients IBD-PD, CBT-based interventions were observed to lead to short-term improvements in disease-related QoL. The impact of CBT on IBD-PD remains unclear due to limitations in study quality and heterogeneity in study design. Further studies are needed to evaluate the efficacy of CBT-based interventions for IBD-PD and to define the role of behavioral interventions delivered within the context of collaborative, biopsychosocial models of care. Expert consensus on best practice for CBT-based interventions and IBD-PD evaluation are needed. Funding Agencies: None